Solar Geometry in Performance of the Built Environment - Miktha Farid Alkadri (A+BE: Architecture and the Built Environment)
As part of the passive design strategy, the development of computational solar envelopes plays a major role to construct a cooperative environmental performance exchange between new buildings and their local contexts. However, the state-of-the-art computational solar envelopes pose a great challenge in understanding site characteristics from a given context. Existing methods predominantly construct 3D context models based on basic architectural geometric shapes, which are often isolated from the surrounding properties of local contexts (i.e., vegetation, materials). Thus, they only focus on context-oriented buildings and energy quantities that unfortunately lack a contextual solar performance analysis. It is clear that this condition may result in a fragmented understanding of the local context during the design and simulation process. With the potential application of attribute point cloud information, it is necessary to consider relevant parameters such as surface and material properties of existing contexts during the simulation of solar geometries, which are currently absent in computational frameworks. As such, the new method is required to enable architects not only to measure specific performances of the local context but also to identify vulnerable areas that may affect the proposed design. This research focuses on exploring an integrated computational design method for solar geometry based on solar and shading envelopes, and geometric and radiometric information from point cloud data. In particular, two computational models consisting of SOLEN (Subtractive Solar Envelopes) and SHADEN (Subtractive Shading Envelopes) are developed, which are applied to temperate and tropical climates, respectively. In design practice, these models help architects to produce informed-design decisions towards high-performed building massing.